Recent Advances in Photocatalytic Removal of Microplastics: Mechanisms, Kinetic Degradation, and Reactor Design - Hamd, Wael; Daher, Elie A.; Tofa, Tajkia Syeed; Dutta, Joydeep (Frontiers in Marine Science, 2022)
Although plastic products are used in almost all aspects of our daily life due to their low cost, portability, durability, and resistance to corrosion and chemicals, they are affecting the environment and life. Thus, the removal and mineralization of microplastics is an important challenge in the 21st century. In recent times advanced oxidation processes (AOPs) is considered to be a potential remediation technology for the degradation of recalcitrant organic molecules and polymers. However, information on kinetic degradation mechanisms and photocatalytic reactor design is insufficient. In this review, we discuss the fundamentals of photocatalyis and photo Fenton processes and the photocatalytic degradation mechanisms. We also introduce different characterization techniques of the major microplastics pollutants such as (PE, PP, PVC, PS, PMMA, PA66). Finally, a detailed overview about the major existing photocatalytic plants and the scaling up methods of photoreactors are discussed.